Analisis Perumusan Kebijakan Berdasarkan Bukti dari Pengembangan Lumpur Lapindo sebagai Destinasi Wisata Gelap di Kabupaten Sidoarjo - Bambang Kusbandrijo; Masadib Akmal Vyandri; Rizkya Dwijayanti (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
The Lapindo Mud Disaster has the potential to be developed into a dark tourism destination. This study aims to provide information and evidence for the formulation of policies and models to support the development of Lapindo as a dark tourism site. The analysis employs Creswell and Poth’s spiral analysis. The findings indicate that external factor components—competition, government policy, leadership, and finance—remain weak. Additionally, supply factor components, particularly the development of Lapindo as a dark tourism area, have not been addressed due to the absence of a specific dark tourism policy. Field evidence suggests that Lapindo has the potential to become a dark tourism destination, as it attracts many visitors, yet its sustainability remains uncertain. Therefore, an evidence-based policy must be formulated through a bottom-up, collaborative stakeholder approach. This study utilizes the Gunn & Var model to analyze field data, revealing that existing policies are still broad, top-down in nature, and fail to address the specific needs of dark tourism development. The proposed model enhances the Gunn & Var framework by incorporating a stakeholder synergy indicator, which emphasizes collaboration among five key actors in the formulation, implementation, and evaluation of policies, all under the leadership of regional authorities.